Pushing the limits of applicability of REBCO coated conductor films through fine chemical tuning and nanoengineering of inclusions. Issue 17 (20th April 2018) - Rizzo, F.; Augieri, A.; Kursumovic, A.; Bianchetti, M.; Opherden, L.; Sieger, M.; Hühne, R.; Hänisch, J.; Meledin, A.; Van Tendeloo, G.; MacManus-Driscoll, J. L.; Celentano, G.
Abstract : Tailoring of self-assembled nanoinclusions in the YBCO matrix improves in-temperature and in-field performances. Abstract : An outstanding current carrying performance (namely critical current density, J c ) over a broad temperature range of 10–77 K for magnetic fields up to 12 T is reported for films of YBa2 Cu3 O7− x with Ba2 Y(Nb, Ta)O6 inclusion pinning centres (YBCO-BYNTO) and thicknesses in the range of 220–500 nm. J c values of 10 MA cm −2 were measured at 30 K – 5 T and 10 K – 9 T with a corresponding maximum of the pinning force density at 10 K close to 1 TN m −3 . The system is very flexible regarding properties and microstructure tuning, and the growth window for achieving a particular microstructure is wide, which is very important for industrial processing. Hence, the dependence of J c on the magnetic field angle was readily controlled by fine tuning the pinning microstructure. Transmission electron microscopy (TEM) analysis highlighted that higher growth rates induce more splayed and denser BYNTO nanocolumns with a matching field as high as 5.2 T. Correspondingly, a strong peak at the B || c -axis is noticed when the density of vortices is lower than the nanocolumn density. YBCO-BYNTO is a very robust and reproducible composite system for high-current coated conductors over an extended range of magnetic fields and temperatures.